Interaction of streptococcal plasminogen binding proteins with the host fibrinolytic system - Fulde, Marcus; Steinert, Michael; Bergmann, Simone (Frontiers in Cellular and Infection Microbiology, 2013)
The ability to take advantage of plasminogen and its activated form plasmin is a common mechanism used by commensal as well as pathogenic bacteria in interaction with their respective host. Hence, a huge variety of plasminogen binding proteins and/or activation mechanisms exist. This review solely focuses on the genus Streptococcus and, in particular, on the so-called non-activating plasminogen binding proteins. Based on structural and functional differences, as well as on their mode of surface linkaging, three groups can be assigned: M-(like) proteins, surface displayed cytoplasmatic proteins with enzymatic activities ("moonlighting proteins") and other surface proteins. Here, the plasminogen binding sites and the interaction mechanisms are compared. Recent findings on the functional consequences of these interactions on tissue degradation and immune evasion are summarized.